Epilepsy in children and the risk of drowning. Issue 5 (May 1993) - Kemp, A M; Sibert, J R
Abstract : To clarify the risks of drowning for children with epilepsy we have studied the records of the 306 children who drowned or nearly drowned in the UK in 1988 and 1989. Ten children with incidents related to epilepsy presented over the study period, four of whom drowned. Children with epilepsy had a higher incidence of submersion accidents but no child participating in supervised swimming drowned. Two children died in the bath. Five children had special needs. We conclude that children with epilepsy can enjoy swimming with a friend in a lifeguard supervised swimming pool. They should be encouraged to shower in a non-glass cubicle rather than have a bath. The bathroom should remain unlocked. Children with poorly controlled epilepsy or associated learning difficulties are at a higher risk from all accident trauma. They need a very high level of supervision while swimming and advice should be given on an individual basis according to what is considered realistic for that child.